Hit or Run: Exploring Aggressive and Avoidant Reactions to Interpersonal Provocation Using a Novel Fight-or-Escape Paradigm (FOE) - Beyer, Frederike; Buades-Rotger, Macià; Claes, Marie; Krämer, Ulrike M. (Frontiers in Behavioral Neuroscience, 2017)
Interpersonal provocation presents an approach-avoidance conflict to the provoked person: responding aggressively might yield the joy of retribution, whereas withdrawal can provide safety. Experimental aggression studies typically measure only retaliation intensity, neglecting whether individuals want to confront the provocateur at all. To overcome this shortcoming of previous measures, we developed and validated the Fight-or-Escape paradigm (FOE). The FOE is a competitive reaction time task in which the winner can choose the volume of a sound blast to be directed at his/her opponent. Participants face two ostensible opponents who consistently select either high or low punishments. At the beginning of each trial, subjects are given the chance to avoid the encounter for a limited number of times. In a first experiment (n=27, all women), we found that fear potentiation of the startle response was related to lower scores in a composite measure of aggression and avoidance against the provoking opponent. In a second experiment (n=34, 13 men), we altered the paradigm such that participants faced the opponents in alternating rather than in random order. Participants completed the FOE as well as the Dot-Probe Task (DPT) and the Approach-Avoidance Task (AAT). Subjects with higher approach bias scores in the AAT avoided the provoking opponent less frequently. Hence, individuals with high threat reactivity and low approach motivation displayed more avoidant responses to provocation, whereas participants high in approach motivation were more likely to engage in aggressive interactions when provoked. The FOE is thus a promising laboratory measure of avoidance and aggression.